A Production systems study on Flora Generic Ventures Incorporated - Lerio, Lourberto S.; Medina, Jason James D.; Primicias, Jose Jesus Y. (Diliman, Quezon City College of Engineering, 1996)
Flora Generic Ventures Incorporated is a medium sized exporter/manufacturer of artificial flowers and other decorative products, located at #4 La Trinidad Street, New Manila. The company, being a job-shop / semi-batch manufacturing system, experiences seasonal peaks of demand, suffers from a high incidence of rework, bottlenecks in assembly, high-work-in-process inventory, and a suboptimal plant layout. After further investigation the group attributed the high rework incident to poor quality control systems. Poor quality of raw materials result in wastage. A suboptimal plant layout as well as the company;s "push" system of production resulted in bottlenecks in the assembly area as well as high work-in-process inventory in this area. The study team, after it's assessment of the problems, recommended the creation of a larger sales and marketing staff to find new markets for off-seasons, the institution of TQM and Just In Time production in the assembly section, designed and improved plant layout, prepared a forecast from the demand of the peak season of the incoming year, and an aggregate plan for hiring.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Flora Generic Ventures Incorporated; Floral products; Production engineering